Evaluasi Pelatihan Wisata Ramah Lingkungan dan Digitalisasi pada Desa Sugihmukti, Kecamatan Pasirjambu, Kabupaten Bandung - Fariz, Fariz; Sutjipto, Riza; Pasaribu, Rina Djunita (PORTAL RISET DAN INOVASI PENGABDIAN MASYARAKAT, 2025)
The Faculty of Economics and Business at Telkom University conducted a community service program titled "Evaluation of Eco-Friendly Tourism Training and Digitalization Implementation at Sugihmukti Village, Pasirjambu District, Bandung Regency" with the objective of enhancing sustainable tourism practices and digital capabilities among community members, tourism managers, and village stakeholders. The program commenced with coordination and needs assessment phases to identify material relevance with Sugihmukti Village's characteristics as an emerging eco-tourism destination located at 1,300-2,200 meters above sea level. Implementation encompassed delivery of educational materials based on sustainable tourism principles, hands-on workshops on environmental conservation management, digital marketing and e-commerce training, as well as pre-test and post-test assessments to measure effectiveness. Evaluation results demonstrated significant improvements in participants' understanding of environmental management practices, digital tools for tourism promotion, and sustainable business operations. Post-test results revealed a 52.3% improvement in participants' comprehension of eco-friendly tourism principles, environmental carrying capacity management, and digital marketing strategies. The community service activity successfully built awareness of environmental stewardship, economic sustainability, and digital transformation among stakeholders, promoting the creation of a more competitive and environmentally responsible tourism destination. The program received positive responses with a satisfaction score of 4.3 out of 5 and was deemed to provide substantial impact on Sugihmukti Village's capacity building in achieving the status of an established eco-tourism destination.